1998
DOI: 10.1046/j.1525-1497.1998.cr187.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical risks for women who drink alcohol

Abstract: OBJECTIVE:To summarize for clinicians recent epidemiologic evidence regarding medical risks of alcohol use for women.METHODS: MEDLINE and PsychINFO, 1990 through 1996, were searched using key words "women" or "woman," and "alcohol." MEDLINE was also searched for other specific topics and authors from 1980 through 1996. Data were extracted and reviewed regarding levels of alcohol consumption associated with mortality, cardiovascular disease, alcoholrelated liver disease, injury, osteoporosis, neurologic symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 235 publications
3
97
1
Order By: Relevance
“…20 This may be especially true for women, who are more vulnerable to the toxic effects of alcohol. 21,22 Indeed our data show that women in the AUDIT-C 0 group (abstainers) were at increased risk for new-onset liver disease. With the exception of abstainers (AUDIT-C 0), women's risk for adverse gastrointestinal outcomes increased only in women in the AUDIT-C 9-12 group.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…20 This may be especially true for women, who are more vulnerable to the toxic effects of alcohol. 21,22 Indeed our data show that women in the AUDIT-C 0 group (abstainers) were at increased risk for new-onset liver disease. With the exception of abstainers (AUDIT-C 0), women's risk for adverse gastrointestinal outcomes increased only in women in the AUDIT-C 9-12 group.…”
Section: Discussionmentioning
confidence: 60%
“…This is unexpected given that men had increased risk at lower scores (≥ 5), and women are more vulnerable than men, especially to the hepatotoxic effects of alcohol. 21,22 Several factors may be biasing the results for women in the AUDIT-C 5-8 group to the null. First, even with a sample of over 9,000 women, we had low power to detect rare events (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Further education of the medical community and the general public is warranted regarding the effects on medical conditions and disease management, not just AUD, that can result from exceeding the NIAAA threshold for low-risk alcohol consumption. [31][32][33] Limitations Data on what transpired during the clinic visit was based solely on patient self-report, and thus was subject to recall and impression management biases. Existing evidence for the validity of proxy measures for clinician behavior is limited; however, a review study concluded that patient report is more accurate than provider report or records review.…”
Section: Discussionmentioning
confidence: 99%
“…44 Other studies have suggested that moderate to high alcohol intake causes menstrual irregularities. [45][46][47] In rats, chronic alcohol consumption can lead to ovarian failure. 48 If suppression of ovulation and gonadotropin levels are protective against ovarian cancer as has been hypothesized, 25,26 and if alcohol disrupts these processes, then high levels of alcohol consumption may be protective against ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%